The Ideology of Religious Studies Then and Now: The Author’s View - Fitzgerald, Timothy (Implicit religion, 2020)
I have found it challenging and productive to revisit The Ideology of Religious Studies (IRS) twenty years after its publication. This article outlines the background to, and motivations for, writing IRS. IRS contains various arguments aimed against a complex target: liberal capitalism and agencies that serve to normalise its precepts and practices, particularly religious studies and the social sciences more widely. IRS was an early stage in a longer-term project - critical religion - that is still evolving. A core part of the argument was and is that the invention of generic religion and its binary opposite the non-religious secular operates rhetorically to make capitalism and liberal Individualism seem “natural,” with a mask of scientific objectivity, normality and respectability. However, I see retrospectively that there are two potentially antagonistic projects in IRS - limited critique and extended critique - which need to be analytically distinguished. This distinction may help to explain some differences in the responses of contributors.